Reviews (Modern theology, 1990)
Book reviewed in this article: Binding the Strong Man: A Political Reading of Mark's Story of Jesus, by Ched Myers, Maryknoll The Threshold of Theology, edited by Paul Avis. Marshall Pickering Kierkegaard's Dialectic of Imagination, by David J. Gouwens, Peter Lang Water into Wine? An Investigation of the Concept of Miracle, by Robert A. H. Larmer, McGill-Queen's